Individuals at Risk of Exercise Addiction Have Higher Scores for Depression, ADHD, and Childhood Trauma - Colledge, Flora; Buchner, Ursula; Schmidt, André; Wiesbeck, Gerhard; Lang, Undine; Pühse, Uwe; Gerber, Markus; Walter, Marc (Frontiers in Sports and Active Living, 2022)
Background Exercise addiction is increasingly being recognized as a psychologically and physically burdensome set of symptoms. However, little is known about the psychiatric profiles of individuals who are at risk. It is well established that individuals affected by substance use disorders frequently suffer from depression, ADHD, and experiences of childhood trauma. The aim of this study is to determine whether this pattern of psychiatric disturbance is also present in individuals at risk for exercise addiction. Methods Individuals exercising for 10+ hours/week were divided in to those at risk and not at risk for exercise addiction based on their scores on the Exercise Dependence Scale. Demographic data and scores on the Beck Depression Inventory, a measure for ADHD in adults and the Childhood Trauma Questionnaire were also gathered. Results 123 individuals agreed to participate in the study, and completed the questionnaires.29 (23.6%) of these individuals were classed as at risk for exercise addiction. There was a statistically significant difference between the at-risk and not at-risk groups on the combined dependent variable after controlling for hours of exercise per week, F(3,95)= 10.198, p=0.00, Wilk’s Λ =.756, partial η2 =.244. Compared those not at risk, individuals at risk for exercise addiction had significantly higher scores for symptoms of depression (t(121)=4.944, p=0.000), ADHD (t(121)=2.915, p=0.004) and childhood trauma (t(121)=2.297, p=0.024). Conclusion Our results suggest that exercise addiction may be accompanied by a disturbed psychiatric profile consistent with other addictive disorders. Clinical interviewing in individuals at risk for exercise addiction is a valuable and worthwhile next step in characterizing this phenomenon.